2021
DOI: 10.3126/jom.v4i1.38657
|View full text |Cite
|
Sign up to set email alerts
|

What Motivate Youths to Start a Business: An Empirical Evidence from Eastern Nepal

Abstract: This survey attempted to explore the motivating factors of young entrepreneurs in eastern Nepal to start a business. Primary data were collected from 204 young entrepreneurs from eastern Nepal using a self-administered questionnaire. The collected data were coded, entered, and processed in the Statistical Package for the Social Science (SPSS, version 25). This survey used a quantitative technique to analyze the collected data. The study's findings revealed that most young entrepreneurs of eastern Nepal were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A study examining young people’s reasons for starting a business in Nepal [ 44 ] showed that profit potential, difficulties in finding jobs, but also the desire to do something new through entrepreneurship are the main factors that motivate young people; only a few of them were motivated by the desire to continue the family business. In another study, analyzing both the expectations of young people and the experience gained by young entrepreneurs, Le Nguyen Doan [ 45 ] found that the most important reasons for starting a business were the continuation of family tradition, the need to be independent and the desire to succeed on their own.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…A study examining young people’s reasons for starting a business in Nepal [ 44 ] showed that profit potential, difficulties in finding jobs, but also the desire to do something new through entrepreneurship are the main factors that motivate young people; only a few of them were motivated by the desire to continue the family business. In another study, analyzing both the expectations of young people and the experience gained by young entrepreneurs, Le Nguyen Doan [ 45 ] found that the most important reasons for starting a business were the continuation of family tradition, the need to be independent and the desire to succeed on their own.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%